A novel approach towards chemoselective reduction of nitro to amine. Issue 36 (5th September 2019) - Dasgupta, Hridoydip Ranjan; Mukherjee, Suvodip; Ghosh, Pranab
Graphical abstract: Highlights: Chemo selective reduction. High tolerance to other highly reducible groups. Clean method. Selective reduction of nitro arenes at room temperature. Abstract: Chemo selective reduction of a wide range of aromatic nitro compound has been performed by using inexpensive Zn powder and CuSO4 system in water medium at room temperature. This system has high tolerance to other highly reducible groups present in nitro substance along with high conversation and selectivity. This chemo-selective reduction also provides a facile root for the synthesis of other industrially important fine chemicals or biologically important compounds where other highly reducible groups are present in close proximity to the targeted nitro groups.